KEBIJAKAN HUKUM PIDANA DALAM UPAYA PENANGGULANGAN TINDAK PIDANA DI BIDANG EKONOMI DI INDONESIA - Yoserwan Yoserwan (Masalah-Masalah Hukum, 2011)
In order to overcome crime in economy, there have been several related statues. The success of a statue to reach the goals, it really depends on the criminal law policy contained in the statues. In fact criminal law policy in the statues relates to economic crime is not consistent, synchronized and harmonized with each others. It is proved in the formulating a crime, elements of crime, criminal liability and the punishment. Inconsistency and inharmonic also exist in formulating of its criminal law procedure such as coordination among related law enforcement agencies. In order to support the success of law enforcement of economic criminal law, there should be consistency synchronization and harmonization of regulation related to economic crime. Kata kunci: Kebijakan Hukum Pidana, tindak Pidana Ekonomi